MSME Financial Capacity Development Model (Micro, Small, Medium Enterprises) - Dian Safita; Abdul Kahar; Mustamin Mustamin; Latifah Sukmawati Yuniar (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the financial capacity development model of micro, small, and medium enterprises (MSMEs) fostered by business incubators and its impact on business performance. The research adopts a qualitative approach using a case study method conducted at a business incubator in Palu City. Data were collected through in-depth interviews, observation, and documentation involving incubator managers, financial mentors, and assisted MSME owners. Data analysis was conducted using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The findings reveal that the financial capacity development model implemented by the business incubator effectively encourages changes in MSMEs’ financial behavior following the mentoring process. Initially, MSMEs exhibited low financial capacity, characterized by the absence of systematic financial records, the mixing of personal and business finances, and business decision-making that was not based on financial data. After receiving mentoring, MSMEs began to adopt simple financial record-keeping practices and utilize digital financial technologies. The development of financial capacity has a positive impact on MSME performance, particularly in improving the efficiency and effectiveness of business management, enabling more rational pricing decisions, and enhancing overall business performance. This study highlights the strategic role of business incubators as a business development ecosystem capable of sustainably strengthening MSMEs’ financial capacity through integrated assistance tailored to the actual needs of business owners.